Evaluation of Service Quality in Improving Public Satisfaction at The Population and Civil Registration Service (Disdukcapil) of Makassar City - Iva, Muhammad Irvan Nur; Susilawati, Andi Ceri; Ramadani, Adelia; Tang, Ibunga; Amalia, Nurul (Journal of Tourism Economics and Policy, 2026)
This study aims to evaluate the quality of public services at the Population and Civil Registration Office (Disdukcapil) of Makassar City, focusing on five dimensions of service quality: tangible, reliability, responsiveness, assurance, and empathy. The primary research source is secondary data in the form of a review of literature, articles, journals, regulations, and websites relevant to this study, while interviews with respondents are used as supporting materials. The results indicate that Disdukcapil services have generally been running well, characterized by friendly, consistent, and fair staff attitudes, as well as prioritizing services for the elderly and pregnant women. However, there are still shortcomings in the tangible dimension, such as the lack of information boards at service chairs, which sometimes confuses the public, and in the empathy dimension, where attention to people with disabilities is not optimal. The literature review supports the finding that the empathy dimension is an important indicator of public satisfaction with public services. Thus, although service quality is already positive, improvements in tangible aspects and attention to the special needs of the community are essential for public services to be more inclusive and effective.